PEMBERDAYAAN MASYARAKAT MELALUI PENINGKATAN KUALITAS BIBIT TANAMAN BUAH DENGAN METODE MINI GRAFTING - Susiyanti, Susiyanti; Nurmayulis, Nurmayulis; Mulyati, Sri; Sjaifuddin, Sjaifuddin; Eris, Fitria Riany (Jurnal Pengabdian Dinamika, 2019)
Fruit plants are commodities that can improve people's lives in the long term. One of the problemsin the cultivation of fruit trees is the provision of quality seedlings. Based on these considerations,community service has been carried out under the title "Empowerment of the Cikuya villagecommunity, Serang Regency, through improving the quality of fruit plant seedlings with the Minigrafting method". The Seedlings quality can be obtained through grafting techniques, but theobstacle is the length of time to get the rootstock ready for grafting. The alternative is a minigrafting. Mini grafting technique that is trained for participants is one of the reproductivetechnologies to produce quality seedlings through early grafting techniques. This communityservice program has been running successfully and has contributed 1) giving new insights to theCikuya village farmers group 2) giving participants insights on the basic theory of mini grafting 3)participants can independently supply fruit plant seedlings 4). The Stages of ImplementationInclude 1) Mini Grafting Practices 2) Maintenance of Mini Grafting